Formation of structure of materials of products of gas-turbine construction in nonequilibrium physical and chemical processes - Гречников, Ф. В.; Зарембо, В. И.; Колесников, А. А.; Михеев, В. А.; Сурудин, С. В.; Киселева, О. С. (Eastern-European Journal of Enterprise Technologies, 2013)
Management of physical and chemical processes to produce products and materials with desired properties and homogeneous distribution of the properties of the volume has always been actual goal of any technology cesses. This problem becomes particularly problematic for multistep thermally activated processes involving massive discharge or absorption of energy. These processes include welding, casting products, different types of heat and chemical heat treatment, coating liquid phase, plasma and other methods. The difficulty of managing such processes in real industrial production, usugublyaetsya virtually impossible to completely locally control and influence of. It is known that the properties of finished products in their manufacture are formed depending on the internal state of the material, considering the physical and chemical reactions of mutual exchange, conversion of heat and the different types of energy. However, in industrial practice this fact is considered weak and isolated consideration of the formation properties of products can lead to fatal errors in the implementation process. These shortcomings multiply deprived technological environment based on the physico-chemical evolution of the solid as a result of the effect of various physical fields (thermal, gravitational, electromagnetic, acoustic, etc.).